Design of chalcogen-containing norepinephrines: efficient GPx mimics and strong cytotoxic agents against HeLa cells. (December 2016) - Marset, Azucena; Begines, Paloma; López, Óscar; Maya, Inés; García-Aranda, Natalia; Schwartz, Simó; Abasolo, Ibane; Fernández-Bolaños, José G
Aim: Numerous chronic diseases exhibit multifactorial etiologies, so focusing on a single therapeutic target is usually an inadequate treatment; instead, multi-target drugs are preferred. Herein, a panel of phenolic thioureas and selenoureas were designed as new prototypes against multifactorial diseases concerning antioxidation and cytotoxicity, as a pro-oxidant environment is usually found in such diseases.Results: Selenoureas were excellent antiradical agents and biomimetic catalysts of glutathione peroxidase for the scavenging of H2 O2 . They were also potent and selective cytotoxic agents against cancer cells, in particular HeLa (IC50 2.77–6.13 μM), apoptosis being involved. Selenoureas also reduced oxidative stress in HeLa cells (IC50 = 3.76 μM).Conclusion: Phenolic selenoureas are promising lead structures for the development of drugs targeting multifactorial diseases like cancer.